EMPOWERMENT OF THE PKK MOTHER'S GROUP WITH TRAINING FOR MAKING COMPOST FERTILIZER FROM ORGANIC WASTE USING EM4 - Tahara Dilla Santi (Universitas Muhammadiyah Aceh, 2021)
Garbage is a problem that often arises in environmental areas. The amount of waste generated in the city of Banda Aceh is 576 tons per day, and 64,000 is household waste. Waste management can be started from the household environment, namely by increasing the knowledge of family members in controlling household waste into compost. This fertilizer comes from organic materials with a simple manufacturing technique. Waste management becomes compost fertilizer can improve the community's economy and become a fertilizer center that is productive and environmentally friendly. Meunasah Mon Cut Village, Lhoknga District, Aceh Besar. The generated household waste is still disposed of and has not been utilized optimally. Therefore, the counseling and training program on composting is very useful and provides skills to the community in producing compost. It is hoped that with this community empowerment program, Meunasah Mon Cut Village can turn useless waste into goods of high commercial value such as compost.